Follow-up of breast cancer in primary care vs specialist care: results of an economic evaluation - Grunfeld, E (Nature Publishing Group, 1999)
A randomized controlled trial (RCT) comparing primary-care-centred follow-up of breast cancer patients with the current standard practice of specialist-centred follow-up showed no increase in delay in diagnosing recurrence, and no increase in anxiety or deterioration in health-related quality of life. An economic evaluation of the two schemes of follow-up was conducted concurrent with the RCT. Because the RCT found no difference in the primary clinical outcomes, a cost minimization analysis was conducted. Process measures of the quality of care such as frequency and length of visits were superior in primary care. Costs to patients and to the health service were lower in primary care. There was no difference in total costs of diagnostic tests, with particular tests being performed more frequently in primary care than in specialist care. Data are provided on the average frequency and length of visits, and frequency of diagnostic testing for breast cancer patients during the follow-up period. © 1999 Cancer Research Campaign